The influence of temporomandibular disorders in neck pain and posture. - Silva, Rodrigo Marcel Valentim da; Basilio, Franciane Batista; Costa, Sillwe Capitulino Farias; Freitas, Francisca Sueleide de Carvalho; Medeiros, Elany Pereira de; Melo, Elaine Marques Franco de; Costa, Karinna Sonálya Aires da (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: The temporo mandibular dysfunction is a biomechanical change in the temporomandibular joint that has a multifactorial origin. The masticatory muscles has a great relationship with the body posture through neuromuscular connections. The correct posture is maintained by a harmony in muscle mechanism involving the muscles of the head, neck and shoulder girdle. Therefore changes in these structures may lead to a postural imbalance mainly related to cranio-cervical disorders causing forward head, cervical spine rectification and asymmetric shoulders established in the ATM dysfunction patients. Objective: To investigate the influence of temporomandibular disorders in neck pain and posture as well as the incidence postural changes. Method: This is a literature review article carried in databases such as Lilacs, Scielo, Medline and Bireme. The studied period was from 2004 to 2015 were used as search terms: temporomandibular joint, the temporomendibular joint syndrome and posture. Among 21 articles initially selected by electronic search in databases, 4 were excluded for the title. We selected 17 studies for a more detailed analysis through the summary, with 3 of them deleted. The remaining 14 articles were evaluated from the text reading. Result: It can be observed that there is a relationship between TMD and postural changes, patients with this disorder have postural deviations such as forward head, increased cervical lordosis and not leveling between his shoulders. Conclusion: Postural changes may be associated with temporomandibular dysfunction, although there are few studies that address physical therapy on the conduct of temporomandibular disorders in pain and posture, we can see that physical therapy is of great importance with positive results in the lives of these individuals .